An Analysis of Japanese Chouon Pronunciation Among Students of Deli Husada Health Institute - Dila Fitria; Dardanila; Lubis, Tasnim (International Journal of Culture and Art Studies, 2025)
This study aims to identify which long vowel sounds (chouon) in Japanese can be easily pronounced and which are difficult for the Deli Husada Institute of Health students in Deli Tua. This research method employs voice analysis using the Praat application to evaluate the students' pronunciation. Praat was used to analyze the duration, frequency, and intensity of participants' voices. The Praat application will record, segment, and analyze the students' voices. The data consists of voice recordings from the six participants when pronouncing vocabulary containing chouon sounds. The findings indicate that there are variations in errors in the pronunciation of certain vowels, such as the vowel /u/ in "yuumei," the vowel /e/ in "meishi" and "heiya," and the vowel /o/ in "ooku," among the students of the Deli Husada Institute of Health. Words with long sounds are also rarely pronounced correctly due to a lack of practice. Vocabulary such as "obaasan," "ojiisan," and "sakkaa" is more often pronounced correctly because they are frequently used in daily learning. Participants who allocated more time to study showed a higher degree of pronunciation similarity to native speakers. Overall, the frequency of usage and conversational learning significantly influence pronunciation ability.